2008
DOI: 10.1002/dmrr.775
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lowering the criterion for impaired fasting glucose on identification of individuals with insulin resistance. The GISIR database.

Abstract: Although neither the ADA2003 nor the ADA1997 definition of IFG appears to be particularly efficacious for the identification of subjects' low insulin sensitivity, lowering the criterion to the ADA2003 glucose threshold increased the sensitivity without affecting the specificity. ADA2003 IFG showed a worse cardiovascular risk profile compared with NFG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The control healthy group were chosen from people coming to the Blood Bank of Isfahan city. Those who had fasting plasma glucose less than 100 mg/dL were enrolled the study [14]. We measured blood pressure at the morning in the supine position and before sample taking.…”
Section: Methodsmentioning
confidence: 99%
“…The control healthy group were chosen from people coming to the Blood Bank of Isfahan city. Those who had fasting plasma glucose less than 100 mg/dL were enrolled the study [14]. We measured blood pressure at the morning in the supine position and before sample taking.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with higher SAG had significantly higher SBP and DBP, and it was found in other studies that in prediabetic hypertensive patients, blood pressure control is less satisfactory than in nondiabetic patients [ 28 , 29 ]. Furthermore, our study found that ALT and AST were higher as the SAG level increased.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with findings in our current review, where the prevalence of i-IFG WHO is at 36.0% and increased to 53.1% for i-IFG ADA . One of the reasons for this change was an attempt to balance the number of IFG and IGT individuals from the prediabetic population [ 85 , 86 ]. However, it has raised considerable discussion among experts worldwide noting that WHO did not lower IFG cut points as set by the ADA [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%